1993
DOI: 10.1038/361369a0
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to cadmium mediated by ubiquitin-dependent proteolysis

Abstract: Cadmium is a potent poison for living cells. In man, chronic exposure to low levels of cadmium results in damage to kidneys and has been linked to neoplastic disease and ageing, and acute exposure can cause damage to a variety of organs and tissues. Cadmium reacts with thiol groups and can substitute for zinc in certain proteins, but the reason for its toxicity in vivo remains uncertain. In eukaryotes, an important selective proteolysis pathway for the elimination of abnormal proteins that are generated under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
144
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(150 citation statements)
references
References 21 publications
6
144
0
Order By: Relevance
“…In addition, we found that VCP plays a critical role in Cd 2+ -induced aggresome formation. The potential for Cd 2+ to induce aggresome formation is supported by the observations that Cd 2+ causes broad protein misfolding and ubiquitination (Jungmann et al, 1993;Nies, 1999;Hall, 2002). Cd 2+ induces protein misfolding mainly through ion substitution and oxidation.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, we found that VCP plays a critical role in Cd 2+ -induced aggresome formation. The potential for Cd 2+ to induce aggresome formation is supported by the observations that Cd 2+ causes broad protein misfolding and ubiquitination (Jungmann et al, 1993;Nies, 1999;Hall, 2002). Cd 2+ induces protein misfolding mainly through ion substitution and oxidation.…”
Section: Discussionsupporting
confidence: 54%
“…Cd 2+ also causes oxidative stress by promoting the formation of free radicals and depleting glutathione, and by binding to sulfhydryl groups of the proteins (Hall, 2002). In addition, Cd 2+ treatment has been shown to enhance the level of ubiquitinated proteins in mammalian and yeast cells (Jungmann et al, 1993;Figueiredo-Pereira and Cohen, 1999) through suppressing both ATP-dependent and -independent protein degradation, but not the protease activities of the 20S proteasome (Figueiredo-Pereira and Cohen, 1999). However, the mechanisms by which Cd 2+ inhibits protein degradation remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…heat shock and cadmium resistance [4,5] and peroxisome bk~genesis [6]. ~ttachment of the highly conserved protein ubiquitin to otl~er eukaryotic proteins targets them for selective degradatioa.…”
Section: Introductionmentioning
confidence: 99%
“…the cyclins) [4,11], transcriptional regulators (e.g. IKB and NF-KB) [7], as well as the abnormal proteins [12], which may arise from mutation or posttranslational damage. In most cases, the ATP-dependent proteolytic pathway is ubiquitin-dependent.…”
Section: Introductionmentioning
confidence: 99%